Impact of adhesive primer and light‐curing on polymerization kinetics of self‐adhesive resin cement in association with free radical reaction. (21st October 2021) - Ozaki, Akane; Shishido, Shunichi; Nakamura, Keisuke; Harada, Akio; Katsuda, Yusuke; Kanno, Taro; Egusa, Hiroshi
Abstract: This study analyzed the impact of adhesive primer and light‐curing on the polymerization kinetics of urethane dimethacrylate‐based self‐adhesive resin cement combined with free radical reaction. Specimens were prepared by mixing the cement paste with or without adhesive primer. Subsequently, specimens were light‐cured or set without light‐curing. The degree of conversion (DC), Vickers hardness (Hv), and free radical concentrations were repeatedly measured up to 168 h after the curing initiation. Irrespective of the curing procedures, DC, Hv, and free radical concentration rapidly increased during the initial 30 min of curing. The specimens cured with adhesive primer and/or light‐curing generally showed higher values of DC, Hv, and radical concentration than those set by chemical curing alone, especially during the initial polymerization phase. Kinetic analysis using a linear mixed model revealed that the adhesive primer had a higher coefficient estimate than light‐curing, indicating that the former had a higher impact on the polymerization. Additionally, the adhesive primer alleviated the Hv reduction caused by water and air during the initial polymerization phase, although light‐curing hardly prevented the polymerization inhibition. Therefore, we suggest that application of adhesive primer is beneficial to achieve higher degree of conversion and better mechanical properties of self‐adhesive resin cements by enhancing free radical reactions.